ASSESSMENT OF TRANSPORT LOGISTICS’ GRADUATES COMPETENCES FROM THE POINT OF VIEW OF EMPLOYERS - Ginavičienė, Jurgita; Piščikienė, Inga; Sprogytė-Bredelienė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The modern logistics business world is changing and presents new challenges to companies, so it is currently necessary to pay attention to the competence of employees, but also to predict which of these competences will be necessary in the future. The aim of the this work was to research the competences of Vilnius College of Technologies and Design Transport Logistics graduates from the point of view of employers. Based on scientific literature and in dept interview of Lithuanian transport and logistics companies’ managers, the article reveals the significance of qualified transport logistics specialists. It presents the analysis of the competences of Vilnius College of Technology and Design Transport Logistics graduates. According to experts, 88.5 percent of Transport Logistics graduates of the Vilnius College of Technology and Design have very good knowledge and skills. They are zealous, possessing not only theoretical but also practical knowledge. They are able to analyse practical situations, not afraid of challenges.